Parental Authority as Observed in the Holy Family of Nazareth and Nowadays - Jan Śledzianowski (Nicolaus Copernicus University in Toruń, 2011)
The Family of Nazareth was not formed according to natural law, yet according to the law revealed by God to Mary (Lu 1: 26-38) and Joseph (Mt 1: 18-24). Obeying the will of Heavenly Father, the spouses, Mary and Joseph, accepted the Son of God as a human being, since Jesus was brought up as the son of Joseph the Carpenter in the city of Nazareth. Jesus was raised under the Law of Moses and Jewish tradition, which stressed respect for parental authority, especially that of a father. The respect for parental authority of St Joseph as the legal father of Jesus (according to Jewish and Roman laws) is manifested through the words uttered by Mary to her 12 year-old son in the Jerusalem Temple: "Son, why hast thou thus dealt with us? Behold, thy father and I have sought thee sorrowing" (Lu 2: 49) - the King James's Bible. Mutual respect between parents, the idea of sharing all the sorrows and joys, especially those connected with the upbringing of their children, is the very foundation of an appropriate development of a young generation.